2020
DOI: 10.3390/d12030106
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Science Confirms the Rarity of Fruit Bat Pollination of Baobab (Adansonia digitata) Flowers in Southern Africa

Abstract: The iconic African baobab tree (Adansonia digitata) has "chiropterophilous" flowers that are adapted for pollination by fruit bats. Although bat pollination of baobabs has been documented in east and west Africa, it has not been confirmed in southern Africa where it has been suggested that hawk moths (Nephele comma) may also be involved in baobab pollination. We used a citizen science approach to monitor baobab tree and flower visitors from dusk till midnight at 23 individual baobab trees over 27 nights during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although previous research, all of it conducted in West or East Africa, has shown that African baobabs are primarily bat‐pollinated (Jaeger, 1945, 1950, 1954; Harris and Baker, 1959; Start, 1972; Ayensu, 1974; Baum et al, 199; Djossa et al, 2015), at our study sites in South Africa we observed high visitation rate of hawkmoths, but no bat visits. The lack of flower‐visiting bats is corroborated by citizen science efforts conducted with local residents (Taylor et al, 2020) and by observations during other flowering seasons by one the authors (SMV). This is not the first time that a plant classified as having a bat pollination syndrome is not, in fact, bat‐pollinated in some populations (Rivera‐Marchand & Ackerman 2006).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although previous research, all of it conducted in West or East Africa, has shown that African baobabs are primarily bat‐pollinated (Jaeger, 1945, 1950, 1954; Harris and Baker, 1959; Start, 1972; Ayensu, 1974; Baum et al, 199; Djossa et al, 2015), at our study sites in South Africa we observed high visitation rate of hawkmoths, but no bat visits. The lack of flower‐visiting bats is corroborated by citizen science efforts conducted with local residents (Taylor et al, 2020) and by observations during other flowering seasons by one the authors (SMV). This is not the first time that a plant classified as having a bat pollination syndrome is not, in fact, bat‐pollinated in some populations (Rivera‐Marchand & Ackerman 2006).…”
Section: Discussionmentioning
confidence: 64%
“…; Coe & Isaac, 1965). In contrast to the abundant work in East and West Africa, we are aware of no documentation of bat pollination of baobabs in Southern Africa and a recent citizen science effort failed to document bat visits to flowers in these populations (Taylor et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Taylor, et al, [35] as the use of chemicals or protecting other species that the moths need in their life cycle. Thus, these results are of importance to policy makers and resource managers ensuring that management decisions take into account the importance of these pollinators.…”
Section: Baobab Tree and Flower Visitorsmentioning
confidence: 99%
“…Moreover, such observations allow to monitor migratory birds, e.g., [ 30 , 31 , 32 , 33 , 34 ]; rare and endangered species, e.g., [ 35 , 36 , 37 , 38 ]; expansion of pests, e.g., [ 20 , 39 , 40 ]; or alien and/or invasive species, e.g., [ 18 , 22 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] as well as colonization of new human-made habitats, e.g., [ 51 ]. In addition, numerous studies show that data collected by amateur scientists allow to describe new interactions between species, e.g., [ 17 , 52 ], to investigate animal phenology, e.g., [ 53 ], and behavior, e.g., [ 54 ], to find changes in species abundance and demography, e.g., [ 55 , 56 , 57 ], and other threats for local fauna and flora being important for nature conservation, e.g., [ 8 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%